Male–Female Differences in the Effects of Age on Performance Measures Recorded for 23 Hours in Mice. (25th June 2021) - Tran, Trang; Mach, John; Gemikonakli, Gizem; Wu, Harry; Allore, Heather; Howlett, Susan E; Little, Christopher B; Hilmer, Sarah N
Abstract: Functional independence is an important aspect of successful aging and differs with age and by sex in humans. Physical performance often declines earlier than other age-associated functional impairments. Rodent models are used to study pharmacological/toxicological effects of human therapies. However, physical outcomes in mice are usually assessed for short periods, with limited information on the influence of age and sex. Here, we investigated how age and sex affected murine physical performance over 23 hours of continuous observation. Young (3 months) and old (22 months) C57BL/6JArc male and female mice were assessed using the Laboratory Animal Behavior Observation, Registration, and Analysis System. Mice were individually housed for recording of distance travelled, mean gait speed, and durations of different physical activities. Compared to young mice of the same sex, old mice travelled significantly shorter distances with slower gait speeds and shorter durations of locomotion, rearing, climbing, and immobility. Older mice groomed significantly more than young mice. Old females reared more during the light cycle than old males. Young females climbed substantially more than young males. Significant Age * Sex interactions were detected for rearing and climbing, whereby an age-related decline was greater in males than in females. Our results suggest that old age reduces exploratory activities and increases grooming in mice. Age-related declines vary between sexes and tend to be greater in males. This noninvasive assessment can be applied to investigate how different interventions affect rodents of different ages and sexes, through the day–night cycle.